Effect of subacute oral toxicity of cypermethrin on biochemical profiles in buffalo calves - SANDHU, H S; BRAR, R S; VERMA, INDU; KAUR, JAGVINDER (The Indian Journal of Animal Sciences, 2014)
Repeated oral administration of a synthetic pyrethroid nsecticide cypermethrin (0.25 mg/kg/day) for 21 consecutive days in male buffalo calves, produced significant decline in the serum levels of triglycerides (16.9-40.2%), HDL cholesterol (42.3%) and VLDL cholesterol (39.1-43.5%) with no change in serum cholesterol levels. Daily ural exposure of cypermethrin produced significant increase in the serum levels of total bilirubin (150.0%), urea (39.7-166.4%) and uric acid (66.7-78.3%). However, no changes in the serum creatinine level were observed in cypermethrin intoxicated buffalo calves.